A SUCCESS STORY REVISITED - John B. Lewis (Wildlife Society Bulletin)
Abstract: Wild turkeys (Meleagris gallopavo) were in serious trouble, especially in the eastern part of the country during the 1940s and 1950s. Years of overharvest, habitat degradation and a total disregard by the public were responsible for the complete loss of wild turkeys in 19 states. Faced with the problem of bringing back the wild turkey, wildlife managers resorted to using game‐farm‐reared turkeys. All of the states attempting to restore turkey populations using game‐farm turkeys reported their efforts failed, except for Michigan. Perfecting the technique of cannon‐netting of native wild turkeys was responsible for what has proved to be a success story unequalled in the annals of wildlife restoration. Wild turkeys are firmly established throughout the U.S. and in Ontario, Canada. The wild turkey's ability in adapting to areas previously thought unsuitable was a complete surprise and contributed to the successful restoration of wild turkey populations during the last half of the 20th century.